Correction: A metabolomic and pharmacokinetic study on the mechanism underlying the lipid-lowering effect of orally administered berberine. Issue 2 (23rd December 2014) - Gu, Shenghua; Cao, Bei; Sun, Runbin; Tang, Yueqing; Paletta, Janice L.; Wu, Xiao-Lei; Liu, Linsheng; Zha, Weibin; Zhao, Chunyan; Li, Yan; Ridlon, Jason M.; Hylemon, Phillip B.; et al.
Abstract : Correction for 'A metabolomic and pharmacokinetic study on the mechanism underlying the lipid-lowering effect of orally administered berberine' by Shenghua Gu et al., Mol. BioSyst., 2015, DOI: ; Web:10.1039/c4mb00500g .